2017
DOI: 10.1017/s1047951117001688
|View full text |Cite
|
Sign up to set email alerts
|

Femoral vein homograft as Sano shunt results in improved pulmonary artery growth after Norwood operation

Abstract: ObjectiveTo evaluate differences in interstage growth of pulmonary arteries between use of polytetrafluoroethylene and femoral vein homograft as Sano shunt during stage-I Norwood palliation.MethodsA retrospective review of all patients who survived to the second stage following Norwood–Sano operation at two institutions was performed. Either polytetrafluoroethylene or the valved segment of femoral vein homograft was used for construction of the Sano shunt. The size of pulmonary arteries was compared at pre-Gle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…We acknowledge that there are a number of technical variations on homograft use, and many centers do not use a composite RVPAS or enshroud the homograft within a constricting stent, and these differences may in part explain our negative results regarding pulmonary arterial growth. However, as suggested by other groups [11], we found that short-term postoperative hemodynamics were somewhat more favorable in the presence of a homograft, including a higher SaO 2 and a lower serum lactic acid concentration. The incidence of extracorporeal membrane oxygenation use and ICU lengths of stay were similar between the groups.…”
Section: Commentsupporting
confidence: 85%
See 3 more Smart Citations
“…We acknowledge that there are a number of technical variations on homograft use, and many centers do not use a composite RVPAS or enshroud the homograft within a constricting stent, and these differences may in part explain our negative results regarding pulmonary arterial growth. However, as suggested by other groups [11], we found that short-term postoperative hemodynamics were somewhat more favorable in the presence of a homograft, including a higher SaO 2 and a lower serum lactic acid concentration. The incidence of extracorporeal membrane oxygenation use and ICU lengths of stay were similar between the groups.…”
Section: Commentsupporting
confidence: 85%
“…The use of a SVH [8][9][10] or FVH [11,12] as part of the S1P has been well described. However, the cumulative published experience with SVHs has been limited to single patient case reports or small case series [9,10,16].…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…5 A noticeable omission is the lack of branch pulmonary artery size data at the time of cardiac catheterization before bidirectional cavopulmonary shunt. Showing better pulmonary artery growth with a valved RV-PA conduit, as others have, 6 would certainly enhance the argument for its use. Finally, the rate of intervention on the conduit is high in comparison with current techniques of nonvalved conduit implantation.…”
mentioning
confidence: 87%